Conflicts over carbon capture and storage in international climate governance - Timmo Krüger (Energy Policy, 2017)
In the Paris Agreement, ambitious emission targets are accompanied by insufficient mitigation measures. It lacks, in particular, strategies on how to reduce the use of fossil fuels. In this context the distinctive prospect of carbon capture and storage (CCS) – reducing emissions, albeit using fossil fuels on a large scale – is of particular interest. CCS technologies promise to solve the climate problem independent of drawn-out political disputes and without changing production and consumption patterns. Conflicts about CCS put the fundamental debate on the agenda, whether a comprehensive transformation of social structures is (un-)necessary and (un-)desired in order to solve the ecological crisis. Therefore, in this paper CCS-conflicts are analyzed with a broader perspective including their effects on general struggles about international climate governance. The key research question is to what extent established social practices and structures become politicized – i.e. challenged. Based on the presented empirical findings, I discuss two theses: First, that the future of climate governance is contingent on decisions about the continued use of fossil fuels. Second, that CCS-conflicts have an explosive force that could lead to massive cracks within the paradigm of ecological modernization and thus could politicize international climate policy.
Keywords: 710; Carbon capture and storage (CCS); Climate governance; Climate politics; Ecological modernization; Fossil fuels; Techno-fix